The university high school of the University of the Eastern Philippines in Northern Samar a descriptive analysis - Mangada, Leah Moore 1936-
This study analyzes the school's organizational structure, faculty qualifications, student population characteristics, and curricular programs from 1970 to 1975. The University High School began as the Catarman Farm School in June 1918 holding intermediate classes until 1919 to produce its first batch of high school students. Upon dropping its intermediate offerings, it became the Catarman Agricultural High School until 1951 when RA 320 made it the Catarman National Agricultural High School. In 1956, RA 1434 reconstituted it into the Samar Institute of Technology (SIT) offering college courses. The high school became the Secondary Department. SIT became a state university in 1964, with two high schools, with the Agricultural High School acting as a laboratory school of the College of Agricultural Education, and a College Preparatory High School. The two schools were fused in 1974-75.